2020
DOI: 10.1136/heartjnl-2020-317672
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical outcomes of triglyceride deposit cardiomyovasculopathy among haemodialysis patients

Abstract: ObjectiveTo evaluate the effect of triglyceride deposit cardiomyovasculopathy (TGCV) on the cardiovascular outcomes in haemodialysis (HD) patients with suspected coronary artery disease (CAD).MethodsThis retrospective single-centre observational study included data from the cardiac catheter database of Narita Memorial Hospital between April 2011 and March 2017. Among 654 consecutive patients on HD, the data for 83 patients with suspected CAD who underwent both [123I]-β-methyl-iodophenyl-pentadecanoic acid scin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Then, TGCV was encoded in the Orphanet (ORPHA code: 565612). Excessive TG accumulation in the myocardium and smooth muscle cells results in various complications including heart failure, cardiomyopathy, arrhythmia, coronary artery disease, chronic kidney disease, and skeletal muscle myopathy [12][13][14], all of which determine a poor prognosis. Early phase clinical trials with a novel orphan drug, CNT-01, have been successfully completed in Japan [15].…”
Section: Introductionmentioning
confidence: 99%
“…Then, TGCV was encoded in the Orphanet (ORPHA code: 565612). Excessive TG accumulation in the myocardium and smooth muscle cells results in various complications including heart failure, cardiomyopathy, arrhythmia, coronary artery disease, chronic kidney disease, and skeletal muscle myopathy [12][13][14], all of which determine a poor prognosis. Early phase clinical trials with a novel orphan drug, CNT-01, have been successfully completed in Japan [15].…”
Section: Introductionmentioning
confidence: 99%
“…TGCV is a metabolic disease characterized by excessive triglyceride deposit accumulation in the heart or vessels and has a high target vessel revascularization rate and poor prognosis. 17 , 18 It has been reported that the factors relevant to coronary stent restenosis, including vascular endothelial growth factor-alpha, transforming growth factor-beta, and interleukin-6, exhibit distinct expression levels in mouse models of TGCV compared with those in the wild-type mice, which may influence the pathophysiology and treatment of CLTI, but the details are unknown. 19 Therefore, we considered that enforcing EVT against the occluded bypass graft would reocclude it; we used the Rheocarna first.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Recently, we reported a higher prevalence of TGCV in hemodialysis patients and the severe clinical outcomes of these patients, irrespective of the presence or absence of diabetes mellitus. 10 Patients with CKD have abnormal TG metabolism and suffer from cardiovascular diseases. Injuries of glomerular endothelial cells play a role in the early stages of CKD.…”
Section: Discussionmentioning
confidence: 99%